Business cycles - Hayek, Friedrich A. von (Friedrich August), 1899-1992.; Klausinger, Hansjörg. (Chicago : University of Chicago Press, 2012)
In the years following its publication, F.A. Hayek's pioneering work on business cycles was regarded as an important challenge to what was later known as Keynesian macroeconomics. Today, as debates rage on over the monetary origins of the current economic and financial crisis, economists are once again paying heed to Hayek's thoughts on the repercussions of excessive central bank interventions. The latest editions in the University of Chicago Press's ongoing series The Collected Works of F.A. Hayek, Business Cycles, Part I contains Hayek's two major contributions on the topic: Monetary Theory and the Trade Cycle and Prices and Production. Moving away from the classical emphasis on equilibrium analysis, Hayek demonstrates that business cycles are generated by the adaptation of the structure of production to changes in relative demand. Thus, when central banks artificially lower interest rates, the result is a misallocation of capital and the creation of asset bubbles and additional instability.
Part 2 [v.2]. Editorial Foreword; Introduction; One: Investigations into Monetary Theory; Appendix: The Exchange Value of Money; A Review; Two: The Purchasing Power of the Consumer and the Depression; Three: A Note on the Development of the Doctrine of 'Forced Saving'; Four: The Present State and Immediate Prospects of the Study of Industrial Fluctuations; Five: Restoring the Price -- Level?; Appendix: Excerpt from a Letter, F.A. Hayek to Gottfried Haberler, December 20, 1931; Six: Capital and Industrial Fluctuations: A Reply to a Criticism; Seven: Investment that Raises the Demand for Capital. Eight: Profits, Interest and Investment. Nine: The Ricardo Effect; Ten: Professor Hayek and the Concertina -- Effect, by Nicholas Kaldor; A Comment; Postscript, by Nicholas Kaldor; Postscript; Eleven: Three Elucidations of the Ricardo Effect; Twelve: The Flow of Goods and Services; Index.
Includes bibliographical references and indexes.
Keywords: Business cycles; Prices; Money